Evidence for the Effectiveness and Acceptability of e-SBI or e-SBIRT in the Management of Alcohol and Illicit Substance Use in Pregnant and Post-partum Women - Wouldes, Trecia A.; Crawford, Andi; Stevens, Suzanne; Stasiak, Karolina (Frontiers in Psychiatry, 2021)
Alcohol and illicit psychoactive drug use during pregnancy have increased worldwide, putting women and their children's health and development at risk. Multiple drug use, comorbid psychiatric disorders, sexual and physical abuse are common in women who use alcohol and drugs during pregnancy. The effects on the mother include poor reproductive and life-long health, legal, family, and social problems. Additionally, the exposed child is at increased risk of long-term physical health, mental health, and developmental problems. The stigma associated with substance use during pregnancy and some clinicians' reticence to inquire about substance use means many women are not receiving adequate prenatal, substance abuse, and mental health care. Evidence for mHealth apps to provide health care for pregnant and post-partum women reveal the usability and effectiveness of these apps to reduce gestational weight gain, improve nutrition, promote smoking cessation and manage gestational diabetes mellitus, and treat depression and anxiety. Emerging evidence suggests mHealth technology using a public health approach of electronic screening, brief intervention, or referral to treatment (e-SBIRT) for substance use or abuse can overcome the typical barriers preventing women from receiving treatment for alcohol and drug use during pregnancy. This brief intervention delivered through a mobile device may be equally effective as SBIRT delivered by a health care professional in preventing maternal drug use, minimizing the effects to the exposed child, and providing a pathway to therapeutic options for a substance use disorder. However, larger studies in more diverse settings with women who have co-morbid mental illness and a constellation of social risk factors that are frequently associated with substance use disorders are needed.